Genetic Factors Associated with Response to Vitamin E Treatment in NAFLD - Mehtap Civelek; Maren C. Podszun (Antioxidants, 2022)
Non-alcoholic fatty liver disease (NAFLD) is becoming the predominant liver disease worldwide, and vitamin E has been clinically shown to improve histological parameters in a subset of patients. In this narrative review, we investigate whether genetic factors may help to explain why some patients show histological improvements upon high-dose alpha-tocopherol (αT) treatment while others do not. In summary, we identified two factors that are associated with treatment response, including genetic variations in haptoglobin as well as fatty acid desaturase 1/2 (FADS1/FADS2). Other genetic variants such as in alpha-tocopherol transfer protein (αTTP), tocopherol associated protein (TAP), transmembrane 6 superfamily 2 (TM6SF2), cluster of differentiation 36 (CD36), and proteins involved in lipoprotein metabolism may also play a role, but have not yet been investigated in a clinical context. We propose to further validate these associations in larger populations, to then use them as a clinical tool to identify the subset of patients that will benefit the most from vitamin E supplementation.